Determination of the Plasma Levels of Growth Arrest Specific 6 in Colon Cancer Patients - BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2023)
Objective: Growth arrest-specific 6 (GAS 6) has a role in cell proliferation and was detected in different cancer types. The aim of this study was to evaluate the plasma GAS 6 levels in colon cancer patients. Methods: This was a prospective study and conducted in a research and training hospital in Turkey. Thirty-three healthy volunteers were enrolled in the control group, thirty-three colon cancer patients who were diagnosed with colon cancer for the first time. Sociodemographic characteristics of participants were recorded. Blood samples of the control group were taken once a time. Patients’ blood samples were taken before and one month after surgery. Results: There were no statistically significant differences between the sociodemographic characteristics of the two groups. The mean plasma GAS 6 levels in control were significantly higher than that of colon cancer patients (p<.0001). There is a statistically significant increase in GAS 6 values after surgery (p<.0001). Conclusion: It was observed that plasma GAS 6 levels of the patients were lower than the control group and were elevated after surgery. We think that our study will contribute to the literature in addition to studies showing that GAS 6 levels may be associated with survival and prognosis in different cancer types. Keywords: Colon cancer, growth arrest-specific 6, patient, plasma levels
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Colon cancer; growth arrest-specific 6; patient; plasma levels